2021
DOI: 10.21037/tgh-2019-rld-10
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in Wilson disease

Abstract: Wilson disease (WD) is rare genetic disorder that presents with varied phenotype that can at times make the diagnosis challenging. Medical treatments are available, but there are still unmet needs for patients. Since life-long therapy is necessary, adherence to medical therapy and best practices for monitoring and individualizing therapy continue to evolve. Studies are ongoing that address some of these issues. In the current review we focused our attention to recent advances in the diagnosis of WD, current me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Similarly, no ALT or AST values are available in copper workers. Wilson disease is a genetic disorder of the liver leading to hepatic copper accumulation [3,4], and the earlier termed Indian childhood diseases were in fact cases of Wilson disease rather than caused by exposure to exogenous copper in drinking water or milk as previously assumed by error [114]. Experimental studies in animals showed mostly unchanged or in rare cases slightly increased serum ALT and AST activities after application of high copper amounts [118][119][120].…”
Section: Coppermentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, no ALT or AST values are available in copper workers. Wilson disease is a genetic disorder of the liver leading to hepatic copper accumulation [3,4], and the earlier termed Indian childhood diseases were in fact cases of Wilson disease rather than caused by exposure to exogenous copper in drinking water or milk as previously assumed by error [114]. Experimental studies in animals showed mostly unchanged or in rare cases slightly increased serum ALT and AST activities after application of high copper amounts [118][119][120].…”
Section: Coppermentioning
confidence: 99%
“…Severe liver injury may be caused be a variety of chemicals of either exogenous or even endogenous origin, which are commonly the result of hereditary metabolic abnormalities leading to accumulation of toxic chemicals. As an example, toxic endogenous chemicals such as iron are found in severe liver diseases like primary hemochromatosis due to genetic overload of iron [1,2], Wilson disease caused by copper overload [3,4], metabolic diseases associated with disturbances of the porphyrin metabolism [5], or the broad spectrum of pediatric liver diseases based on genetic background [6]. As opposed, particular challenges in experimental studies and clinical practice are liver injuries caused by exogenous chemicals such as alcohol [7,8], occupational and household organic chemicals [9], pollutants and contaminants [10][11][12], nature based products like mushrooms [13], conventional drugs [8,14,15] and finally herbs including herbal medicines [8,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of cell transplantation for the patients with liver metabolic disorder syndrome, [10][11][12] ammonium metabolism is particularly necessary for clinical application. In urea cycle abnormality, patients usually have hyperammonemia, while other liver functions are preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Methanobactins (Mbns) are copper-chelating natural products produced by some species of methanotrophs, methane-oxidizing bacteria that depend on copper as a cofactor for their primary metabolic enzyme, particulate methane monooxygenase (pMMO) . Under conditions of copper starvation, methanotrophs secrete Mbns to scavenge and import copper from the environment. Due to their high copper binding affinity, Mbns are a promising therapy for Wilson disease, a genetic disorder of copper metabolism typically treated by copper chelation. Mbns are ribosomally produced, post-translationally modified peptides (RiPPs) synthesized by modification of a precursor peptide, MbnA, by a series of biosynthetic enzymes encoded within the Mbn operon. MbnA consists of a core peptide that is converted to mature Mbn and a leader peptide that is cleaved by an unknown mechanism. On the basis of phylogenetic analysis, Mbn operons have been divided into five groups, with methanotrophic Mbns classified in groups I and II .…”
mentioning
confidence: 99%